Dielectric property and molecular structure of grafted epoxy resin - Wong, Yen Wen (Nanyang Technological University, 2024)
Epoxy resin is extensively used in electrical power systems due to its excellent thermal, chemical, and impact resistance, low shrinkage and favourable strength-to-weight ratio. Studies have shown the enhanced electrical properties of grafted crosslinked polyethylene (XLPE), yet there has been no attempt to graft epoxy resin. This project aims to bridge the gap by synthesizing grafted epoxy resin using allyl chloroacetate (AC), 2-amino-5-chloro-2′-fluorobenzophenone (ACF) and maleic anhydride (MA) as grafting agents, with a focus on evaluating their dielectric properties and molecular structure pertaining to grafting. Several characterization techniques have been utilized, including Fourier Transform Infrared Spectroscopy (FTIR) to confirm the grafting of grafting agents onto epoxy. In addition, dielectric spectroscopy, resistivity and dielectric breakdown tests have been conducted to determine the dielectric properties of grafted epoxy. Epoxy grafted with ACF exhibits the lowest permittivity and dielectric loss, notably with a reduction of 27% and 41%, respectively, compared to pure epoxy at a power frequency of 50Hz. Furthermore, epoxy grafted with MA demonstrates a significant enhancement in resistivity by 17 times and dielectric breakdown strength by 17%, when compared to pure epoxy. Overall, grafted epoxy resin displayed superior dielectric properties compared to pure epoxy which indicates a promising avenue for enhancing electrical insulation materials.